Effectiveness of Hotel Wastewater Treatment and Economic Benefits of Clean Water from STP-Based Wastewater Treatment Plants - Enda Kartika Sari; Elgha Nur; Setiatriarini Tirtaweningtias (Jurnal Penelitian Pendidikan IPA, 2026)
Wastewater treatment is an important aspect in the hospitality industry, especially to maintain environmental sustainability and meet water quality regulations. This study aims to analyze the effectiveness of the Wastewater Treatment Plant (WWTP) installation at The Zuri Baturaja Hotel using the Sewage Treatment Plant (STP) method. The analysis was carried out by monitoring the chemical parameters of wastewater quality, such as pH, COD, TSS, BOD, Ammonia, Oil and Fat, Total Coliform parameters. Wastewater sampling was carried out in accordance with the SNI 6989.57: 2008 standard to ensure that the treatment results meet the Environmental Quality Standards. This economic assessment of waste management is carried out to evaluate the cost and benefit aspects of waste management with the aim of increasing efficiency, reducing environmental impacts, and utilizing the economic potential of waste. This assessment includes various approaches, depending on the type of waste being managed. Economic assessment of waste is essential to ensure that waste management not only protects the environment but also provides financial benefits to companies and communities.